Compliments of confinements: substitution and dimension induced magnetic origin and band-bending mediated photocatalytic enhancements in Bi1−xDyxFeO3 particulate and fiber nanostructures1. Issue 24 (28th June 2015) - Sakar, M.; Balakumar, S.; Saravanan, P.; Bharathkumar, S.
<x xml:space="preserve">Abstract</x> We have demonstrated the dimension dependent structural, optical, magnetic and sunlight-driven photocatalytic properties of Dy-substituted BiFeO3 particulate and fiber nanostructures.